1991
DOI: 10.1071/ar9910835
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular-arbuscular mycorrhizae (VAM) improve phosphorus and zinc nutrition and growth of pigeonpea in a Vertisol

Abstract: In a glasshouse trial, pigeonpea (Cajanus cajan) was grown in a Vertisol from the Darling Downs, Qld. The experimental design included two rates of inoculation with vesicular-arbuscular mycorrhizal (VAM) fungi (nil and inoculated), three rates of phosphorus (P) application and two of zinc (Zn), and inoculation (nil and inoculated) with a recently discovered pathogen of pigeonpea, Phytophthora drechsleri Tucker (Pdr). lnoculation with the pathogen was included in the factorial design to investigate any effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This agrees with results of Wellings et al (1991) who examined different species of VAM fungi. Bowen et al (1974) concluded that the higher absorption of Zn by mycorrhizas was due first to a larger size of ectomycorrhizas compared with uninfected roots, and second to a larger absorbing power of the mycorrhiza surface.…”
Section: The Effect Of Ectomycorrhizal Associations On Zn Distributionsupporting
confidence: 82%
See 1 more Smart Citation
“…This agrees with results of Wellings et al (1991) who examined different species of VAM fungi. Bowen et al (1974) concluded that the higher absorption of Zn by mycorrhizas was due first to a larger size of ectomycorrhizas compared with uninfected roots, and second to a larger absorbing power of the mycorrhiza surface.…”
Section: The Effect Of Ectomycorrhizal Associations On Zn Distributionsupporting
confidence: 82%
“…As well as major nutrients, this involves the uptake of trace elements such as Zn, which can be increased by mycorrhizal associations (Wellings et al, 1991). Zn deficiency of nonmycorrhizal plants is caused by the low mobility of Zn in the soil and the development of depletion zones around the roots .…”
Section: Introductionmentioning
confidence: 99%
“…A beneficial effect of mycorrhizal colonization on Zn uptake has been shown for maize (Faber et al 1990;Liu et al 2000;Sharma et al 1992), pigneonpea (Wellings et al 1991), wheat (Khare et al 1998;Ryan and Angus 2003) and wetland rice (Purakayastha and Chhonkar 2001). Upon colonization, the mycelium of the AMF increases the nutrient absorbing surface area of the symbiosis, enhances exploration of a larger soil volume and thereby increases uptake, specifically of immobile nutrients such as P and Zn (Smith and Read 1997).…”
Section: Introductionmentioning
confidence: 92%
“…A large number of studies demonstrate the beneficial effect of AM fungi on Zn uptake by the host plants, including lowland rice (Purakayastha and Chhonkar 2001), pigeon pea (Wellings et al 1991), wheat (Ryan and Angus 2003), and tomato (Cavagnaro et al 2010). The effects are mostly reported for plants grown in soils with low Zn availability.…”
Section: Role Of Mycorrhizaementioning
confidence: 99%